SEMANTIC FUNCTION OF ANTHROPONYMS USED IN O‘TKIR HOSHIMOV’S SHORT STORY ODAM OVOZI - S.B.Khursankulov; D.Z.Abduazimova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article analyzes the linguopoetic and semantic features of anthroponyms used in the short story “The Voice of Man” by O‘tkir Hoshimov. It substantiates that the names occurring in the story, such as Mastura, Yo‘ldoshali, Asqarjon, Lola, and Zamira, function not only as nominative units but also as important artistic and aesthetic devices. Furthermore, the study examines how anthroponyms contribute to the representation of social issues, particularly the relationships between parents and children, on a scientific basis. As a result of the research, the functional significance of anthroponyms in enhancing the overall linguopoetic expressiveness of the text is identified.